INNOVATIVE METHODS FOR INCREASING WAREHOUSE CAPACITY: INNOVATIVE METHODS FOR INCREASING WAREHOUSE CAPACITY - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Warehouse operations are much more complex than when they appear at first glance. Profiling (partitioning) of products and orders leads to a potential multitude of warehouses inside the warehouse. The paper presents an algorithm for increasing storage capacity in modern warehouses.